Dynamic Traction of Deep-Sea Polymetallic Nodule Collector - Yuheng Song; Shiyang Yin; Ning Zhang; Fengnian Lu; Zexuan Cheng (Journal of Marine Science and Engineering, 2023)
The ocean is extremely rich in mineral resources. To cope with the shortage of land mineral resources, countries are focusing on the development of deep-sea mineral mining technology. Owing to its superior traction performance, the deep-sea polymetallic nodule collector (DPNC) has become the preferred solution for ocean mining. This paper proposes a dynamic traction calculation model to address the shortcomings in the classical static traction calculation model with consideration of the dynamic variation rule of grouser–soil interaction in the DPNC process. Lab tests were conducted to formulate materials similar to deep-sea soil, and the corresponding shear stress–displacement models were established using the discrete element method (DEM) and Magic Formula to describe the “shear stress–displacement” relationship more accurately. Considering Kunlong 500, which is a Chinese DPNC, as an example, the periodicity and dynamics of the dynamic traction force were analyzed and compared with the numerical simulation results. The dynamic traction force was smaller than the static traction force and fluctuated significantly when considering the dynamic grousers–soil interaction. The magnitude and fluctuation of the dynamic traction force were influenced by the ratio of the grouser height to the spacing. In the DPNC design, the ratio of the grouser height to the spacing should be optimized according to the properties of the deep-sea subsoil to improve the traction performance and stability of the DPNC.